Demographics, Awareness and Pattern of Diabetic Retinopathy among Diabetic Patients - Basnet, Anjila; Byanju, Raghunandan; Thapa, Samir; Shah, Sanjit Kumar; Simkhada, Suman (Journal of Nobel Medical College, 2024)
Background: Diabetic retinopathy is one of the emerging causes of blindness in developing countries. This study was carried out among diabetic patients to determine the demographics, severity of diabetic retinopathy and also to assess the level of awareness of diabetic eye disease. Materials and Methods: The data, which were collected prospectively from self-designed proforma, we analyzed by using the Statistical Package for the Social Sciences (SPSS) VERSION 16. Diabetic retinopathy was graded by clinical examination using Early Treatment Diabetic Retinopathy Study criteria. Results: Two hundred and forty-nine patients were included in the study. The mean age of the patients was 59 years. Mild non-proliferative diabetic retinopathy accounted for 15.7%followed by moderate non-proliferative diabetic retinopathy in 6% and severe non-proliferative diabetic retinopathy in 2.8%. Newar and Chhetri were the predominant ethnic groups, comprising 26.1% and 25.7% respectively. Majority of the patients were aware of diabetic retinopathy and its potential for blindness. Conclusion: The occurrence of diabetic retinopathy was found to be higher than other studies done in similar settings. Majority of the patients were aware of diabetic retinopathy and its potential for blindness and the source of awareness was from the health professionals.